Compulsive Sexual Behavior as a Maladaptive Coping Mechanism in Bipolar Affective Disorder: A Case Report - Shafly, Moch Syafirul Nur; Ahadiah, Hayyunah Rohmatul; Syadza, Lailatus; Algristian, Hafid; Setyorini, Dian (Yayasan Sinergi Kawula Muda, 2025)
Compulsive Sexual Behavior (CSB) is increasingly acknowledged as a comorbid feature in individuals with Bipolar Affective Disorder (BAD), particularly during manic episodes. It often presents as a maladaptive coping mechanism for affective instability and unresolved trauma. This case report describes a 31-year-old male diagnosed with BAD and exhibiting chronic compulsive pornography use, social withdrawal, and dependent personality traits. The patient’s compulsive behavior persisted beyond mood episodes and was characterized by a persistent inability to control sexual urges, leading to distress and impaired daily functioning. Developmental history revealed early exposure to family conflict, emotional neglect, and an overdependent relationship with his mother, which contributed to insecure attachment and limited autonomy. The patient used pornography as an emotional escape, particularly during episodes of anxiety, loneliness, or boredom. Psychiatric evaluation confirmed comorbidity with Compulsive Sexual Behavior Disorder (CSBD) based on ICD-11 criteria. Therapeutic intervention included Cognitive Behavioral Therapy (CBT) tailored to address compulsive behavior, emotion regulation deficits, and trauma-related triggers. The patient responded favorably to structured psychoeducation and behavioral strategies, although long-term outcomes remain uncertain due to limited follow-up. This case underscores the complex interplay between CSB and BAD, with implications for diagnosis, treatment planning, and long-term management. It highlights the importance of early recognition of CSB symptoms, the role of trauma-informed care, and the need for integrative therapeutic approaches in patients with dual diagnoses. Clinicians are encouraged to assess compulsive behaviors beyond the scope of mood symptoms and address them as independent therapeutic targets to enhance functional recovery.